2020
DOI: 10.2478/bhk-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neck angles and ground reaction forces in schoolchildren during backpack carriage

Abstract: SummaryStudy aim: This study aimed to examine the effect of carrying backpacks on neck posture and ground reaction forces (GRFs) and to investigate the relationship between neck angles and GRFs during backpack carriage in schoolchildren.Material and methods: The craniohorizontal angle (CHA), craniovertebral angle (CVA), sagittal shoulder posture (SSP) and GRFs were measured in right-handed schoolchildren (14 male and 12 female) with mean age 10.17 ± 1.15 years during loaded and unloading conditions. The Qualis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The review mirrors this trend, though with certain distinctions. Backpacks undeniably cause a reduction in the CV angle, leading to cervical deformation and enhanced shear forces, potentially resulting in abnormal postures like forward head posture [51]. This review also encompasses indices related to cervical spine deformity and demonstrates a similar trend.…”
Section: Discussionmentioning
confidence: 89%
“…The review mirrors this trend, though with certain distinctions. Backpacks undeniably cause a reduction in the CV angle, leading to cervical deformation and enhanced shear forces, potentially resulting in abnormal postures like forward head posture [51]. This review also encompasses indices related to cervical spine deformity and demonstrates a similar trend.…”
Section: Discussionmentioning
confidence: 89%
“…These scholars found that carrying a backpack weighing 15% of the child's body weight changes the position of the head and increases the normalized value of the anterior-posterior shear force. Increasing this force may lead to the development of postural disorders and defects [25]. In addition to heavy books and notebooks, students carry different personal items in their backpacks that increase the backpack's weight.…”
Section: Discussionmentioning
confidence: 99%
“…These bags were used by the students on a daily basis to carry their books to school for a duration of 5 months. For assessing neck, shoulder, and upper back posture, the most commonly used evaluation metrics include the craniovertebral angle, craniohorizontal alignment, and sagittal shoulder positioning (15) . During this time frame, measurements for the CVA, CHA, and SSP assessments were recorded both before and after the period.…”
Section: Methodsmentioning
confidence: 99%